Coupled geomechanical and reactive geochemical model for fluid, heat flow and convective mixing: application for CO2 geological sequestration into saline aquifer with heterogeneity. (2017) - Zhang, Ronglei; Winterfeld, Philip H.; Yin, Xiaolong; Wu, Yu-Shu; Xiong, Yi
The significance of thermal-hydrological-mechanical-chemical (THMC) processes is well-identified in the operation of CO2 geo-sequestration. Geomechanical and geochemical effects may significantly affect aqueous phase composition, porosity and permeability of the formation, which in turn influence fluid advection, convection and transport. A sequentially coupled mathematical algorithm is employed to simulate reactive transport of water, CO2 gas and species in subsurface formation with geomechanics, which is bale to model the THMC processes of the fluid advection and convection, heat and solute transport in aqueous and gaseous phase, mean stress, and geochemical reactions under both equilibrium and kinetic conditions. A 2D model with complex chemical compositions is presented to analyse the THMC processes quantitatively, including geomechamical effect due to CO2 injection, dispersion and convective mixing due to CO2 dissolution, mineral alteration due to chemical reaction of water, CO2 and rock minerals, coupled effects of geochemical reaction and geomechanics.